Phosphorylation, Dephosphorylation, and Multiprotein Assemblies Regulate Dynamic Behavior of Neuronal Cytoskeleton: A Mini-Review - Kurochkina, Natalya; Bhaskar, Manju; Yadav, Sharda Prasad; Pant, Harish C. (Frontiers in Molecular Neuroscience, 2018)
Cellular localization, assembly and abnormal aggregation of neurofilaments depend on phosphorylation. Pathological processes associated with neurodegeneration exhibit aberrant accumulation of microtubule associated aggregated forms of hyperphosphorylated neuronal protein tau in cell bodies. These processes are critical for the disease progression in patients suffering from Alzheimer's disease, Parkinson's disease, and Amyotrophic Lateral Sclerosis. In healthy cells, tau is localized in axons. Topographic regulation suggests that whereas the sites of synthesis of kinases and neurofilaments are the cell bodies, and sites of their functional assemblies are axons, phosphorylation/dephosphorylation are the key processes that arrange the molecules at their precise locations. Phosphorylation sites in the dynamic developmental and degenerative processes differ. Not all these processes are well understood. New advancements identify epigenetic factors involved in AD which account for the influence of age-related environment/genome interactions leading to the disease. Progress in proteomics highlights previously found major proteins and adds more to the list of those involved in AD. New key elements of specificity provide determinants of molecular recognition important for the assembly of macromolecular complexes. In this review, we discuss aberrant spatial distribution of neuronal polypeptides observed in neuropathies: aggregation, association with proteins of the neuronal cytoskeleton, and phosphorylation dependent dynamics. Particularly, we emphasize recent advancements in understanding the function and determinants of specific association of molecules involved in Alzheimer’s disease with respect to the topographic regulation of phosphorylation in neuronal cytoskeleton and implications for the design of new therapies. Further, we address the role of various filament systems in maintenance of the shape, rigidity and dynamics of the cytoskeleton.